Ocular changes and general condition in lupus erythematosus (SLE) – own observation - Brydak-Godowska, Joanna (Klinika Oczna / Acta Ophthalmologica Polonica, 2007)
The aim of the study was to assess ocular manifestations in patients with systemic lupus erythematosus (SLE). The following, were included in the evaluation: clinical condition, duration of the disease and treatment used. The study was performed in 100 patients with SLE. Evaluation of the clinical condition and opththalmoscopic findings in patients with SLE demonstrated abnormal Schirmer tests in 41% patients, scleritis 2%, retinopathy 7% and neuritis 1%. Inflammatory changes in the anterior segment of the eyeball, neuritis and retinopathy occurred solely in the phase of exacerbation. Adverse events observed after treatment with chloroquine or prednisone (chloroquine maculopathy, cataract, glaucoma) are related to dosage and duration of the treatment.